1999
DOI: 10.1093/humrep/14.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum progesterone on the day of HCG administration in IVF is associated with a higher pregnancy rate in polycystic ovary syndrome

Abstract: Our study compared 84 patients with polycystic ovary syndrome (PCOS) with 84 control patients who had normal ovaries and who were matched for the main determinants of success in in-vitro fertilization (IVF) and embryo transfer. Serum concentrations of oestradiol and progesterone on the day of human chorionic gonadotrophin (HCG) injection were significantly higher in PCOS than in normal patients (oestradiol 2016 +/- 1.8 pg/ml versus 1456 +/- 40.9 pg/ml, P < 0.01; progesterone 1.6 +/- 0.1 ng/ml versus 1.2 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 21 publications
1
45
1
4
Order By: Relevance
“…At present, there is no consensus on whether P elevation is associated with the achievement of pregnancy. Several studies have denied the presence of such an association (7)(8)(9)(10)(11)(12)(13)(14)(15), others have confirmed the presence of a negative association between P elevation and PRs (16)(17)(18)(19)(20), and yet others have found a favorable effect on pregnancy outcome (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no consensus on whether P elevation is associated with the achievement of pregnancy. Several studies have denied the presence of such an association (7)(8)(9)(10)(11)(12)(13)(14)(15), others have confirmed the presence of a negative association between P elevation and PRs (16)(17)(18)(19)(20), and yet others have found a favorable effect on pregnancy outcome (21).…”
mentioning
confidence: 99%
“…Yet in the late follicular phase, the secretion of P and the number of mature follicles correlate positively (22,23). Therefore, it is reasonable to hypothesize that the P levels at the end of COH tend to be higher in patients with a good ovarian response (21). The raised peripheral concentrations of P in the late follicular phase are likely to influence the secretory changes of the endometrium, leading to impaired endometrial receptivity (24).…”
mentioning
confidence: 99%
“…Bosch and colleagues (10) established a discriminatory P concentration of 1.2 ng/mL as an indicator of premature luteinization, as did Doldi et al (7). In the present study, a P level of R1.3 ng/mL was used as the discriminatory value for premature luteinization.…”
Section: Premature Luteinizationmentioning
confidence: 52%
“…For example, Fanchin et al (6) observed premature elevation of P before hCG administration and suggested that endometrial receptivity may be affected as a result. Other studies have reported better pregnancy outcome when P levels are increased (7).…”
mentioning
confidence: 85%
“…The classification of the disease is based on both clinical and endocrine features with a well known ultrasound ovarian pattern, obesity, menstrual cycle disturbances, hyperandrogenaemia, chronic anovulation, abnormal gonadotrophin secretion and hyperinsulinemia [9,10] .…”
Section: Introductionmentioning
confidence: 99%